A unique BRCA1 mutation identified in Mongolia. Issue 3 (1st May 2001) - Elit, L.; Jack, E.; Kwan, E.; Baigal, G.; Narod, S.
Abstract : This is a case report of genetic assessment conducted on a family residing in the third world where two sisters have presented with early onset ovarian cancer. Protein truncation testing and DNA sequencing identified a unique mutation on exon 11 (3452delA) of the BRCA1 gene. Buccal swab testing of three siblings and three offspring showed that half of the family members carried the same mutation. Currently, genetic testing in third-world countries is conducted within research budgets, as testing is not affordable or locally available for such high-risk families. Unique mutations in the BRCA1 gene that are expressed in geographically isolated groups will be useful in genetic counseling and preventative maneuvers. The only preventive management strategy available in the third world is prophylactic surgery.